2006
DOI: 10.1103/physrevd.73.064012
|View full text |Cite
|
Sign up to set email alerts
|

Gravitationally induced quantum superposition reduction with large extra dimensions

Abstract: A gravity-driven mechanism ("objective reduction") proposed to explain quantum state reduction is analyzed in light of the possible existence of large extra dimensions in the ADD scenario. By calculating order-of-magnitude estimates for nucleon superpositions, it is shown that if the mechanism at question is correct, constraints may be placed on the number and size of extra dimensions. Hence, measurement of superposition collapse times (e.g. through diffraction or reflection experiments) could represent a new … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Indeed, it has been shown that the compactification radii have grown by less than a factor of ten in size over the history of the solar system [36]. Also, the variation of G(t) is also independent of the possible existence of extra dimensions.…”
Section: Evolution Of Consciousness and Time Dependent Ledsmentioning
confidence: 98%
See 2 more Smart Citations
“…Indeed, it has been shown that the compactification radii have grown by less than a factor of ten in size over the history of the solar system [36]. Also, the variation of G(t) is also independent of the possible existence of extra dimensions.…”
Section: Evolution Of Consciousness and Time Dependent Ledsmentioning
confidence: 98%
“…Of course, the time scales required for a significant change in the value of G(t) are on the order of a fraction of the age of the Universe, which most likely would surpass the "biological" time of species on the Earth. Indeed, it has been shown that the compactification radii have grown by less than a factor of ten in size over the history of the solar system [36]. Also, the variation of G(t) is also independent of the possible existence of extra dimensions.…”
Section: Evolution Of Consciousness and Time Dependent Ledsmentioning
confidence: 99%
See 1 more Smart Citation